Bleanded Learning dengan Model Pembelajaran Maraja - Anita Puspita; Arsad Bahri; Rahmawati Latif (Biology Teaching and Learning, 2022)
Abstract. Online learning that was carried out during the Covid-19 pandemic had various limitations. One alternative that can be a learning solution is the implementation of limited face-to-face learning. However, the implementation of limited face-to-face learning has weaknesses, including a lack of learning time allocation because the number of face-to-face hours has decreased. On the other hand, giving group assignments in online learning raises the phenomenon of male students' inactivity and completely leaves it to female students to do group assignments. By looking at this phenomenon, we need a learning model that can give freedom to students to develop their critical thinking skills. So, learning that is considered to be able to overcome these weaknesses is learning with Blended Learning with the MARAJA learning model. The MARAJA learning model is a learning model that focuses on increasing the effectiveness of the biology learning process, increasing male students' learning motivation, and increasing students' critical thinking skills. The MARAJA Learning Model consists of 4 stages namely (1) Starting from self and Analysis, (2) Action Plans and Applications in content, (3) Explaining Content, and (4) Appreciation. The approach used in this study is a library approach, with data collection methods in the form of documents in the form of books, literature and scientific journals related to the topics written in this article. The data analysis technique used is an interactive analysis technique consisting of three steps, namely data reduction, data display and data verification.Keywords: blended learning, MARAJA learning model, critical thinking, motivation, learning effectiveness.